Big night - Rysher Entertainment ([United States] Rysher Entertainment, 1996)
The story of two brothers whose Italian restaurant is on the brink of bankruptcy. Their only chance for success is to risk everything they own on an extravagant feast for bandleader Louis Prima. But their big night is complicated by a lovers' triangle, a sneaky restaurant rival, and the hilarious perfection of chef Primo.
VHS.
Stanley Tucci, Campbell Scott, co-producers ; produced by Jonathan Filley ; written by Stanley Tucci & Joseph Tropiano ; directed by Stanley Tucci & Campbell Scott.
Isabella Rosellini, Tony Shalhoub, Stanley Tucci.
Keywords: Comedy films; Feature films